Eco-oriented agriculture as a development driver of inclusive agribusiness - Степаненко, С. В.; Крюкова, І. О.; Власенко, Т. А. (Economics of Development, 2023)
The relevance of the research is determined by the need to ensure food security, which led to the search for new models and forms of agricultural development. Among such forms inclusive models of agrarian business occupy a special place as today they are recognized as capable of solving the problems of poverty, inequality and overcoming hunger. The purpose of the research is to substantiate the mechanism of how to manage ecologically-oriented agrarian business as one of the drivers of inclusiveness, and further develop directions of organic agricultural production. When writing the article, the author used the following methods of scientific knowledge: monographic, analysis and synthesis, systematic approach, comparison, scientific-abstract systematization and concretization. Based on the results of the research, key trends and drivers of agricultural development have been revealed. The set of basic forms of inclusive agrarian business organization has been studied. A level system of standards of products, works and services for the industry has been substantiated. The author’s model of the institutional mechanism for managing ecologically-oriented agricultural production, with the certification and standardization of organic produce being the key elements of it, has been proposed. The current state of development of organic production has been studied, the structure of export of organic produce has been analyzed. It has been determined that Ukrainian organic agriculture has a significant potential for its future development and is important for the European food market. Prospective benchmarks for further development of organic production in terms of ecologically-oriented types of agrarian business have been substantiated. The results of the research can be used by all agricultural enterprises that search for new approaches to management and strive to increase the competitiveness of agricultural produce in modern conditions of transition to the concept of sustainable development. Актуальність дослідження зумовлена необхідністю забезпечення продовольчої безпеки, яка призвела до пошуку нових моделей і форм розвитку сільського господарства. Серед таких форм особливе місце займають інклюзивні моделі аграрного бізнесу, які сьогодні визнані спроможними до вирішення проблем бідності, нерівності та подолання голоду. Мета дослідження полягала в обґрунтуванні механізму управління еколого-орієнтованим аграрним бізнесом, як одного з драйверів інклюзивності, та напрямів подальшого розвитку органічного аграрного виробництва. При написанні статті було використано методи наукового пізнання: монографічний, аналіз і синтез, системний підхід, порівняння, науково-абстрактної систематизації і конкретизації. За результатами дослідження виявлено ключові тренди і драйвери розвитку сільського господарства. Досліджено сукупність основних форм організації інклюзивного аграрного бізнесу. Обґрунтована рівнева система стандартів продукції, робіт і послуг для галузі. Запропонована авторська модель інституційного механізму управління еколого-орієнтованим аграрним виробництвом, ключовими елементами якого є сертифікація і стандартизація органічної продукції. Досліджено сучасний стан розвитку органічного виробництва, проаналізована структура експорту органічної продукції. Визначено, що українське органічне сільське господарство має значний потенціал його майбутнього розвитку та є важливим для європейського ринку продовольства. Обґрунтовано перспективні орієнтири подальшого розвитку органічного виробництва у розрізі видів еколого-орієнтованих видів аграрного бізнесу. Результати дослідження можуть бути використані усіма аграрними підприємствами, які здійснюють пошук нових підходів до управління та прагнуть до підвищення конкурентоспроможності аграрної продукції у сучасних умовах переходу до концепції сталого розвитку.
Еколого-орієнтоване сільське господарство як драйвер розвитку інклюзивного агробізнесу
Keywords: agrarian business; organic production; certification; agricultural producers; management mechanism; аграрний бізнес; органічне виробництво; сертифікація; агровиробники; механізм управління